EVALUATING THE QUALITY OF ISLAMIC RELIGIOUS EDUCATION USING THE CIPP (CONTEXT, INPUT, PROCESS, PRODUCT) MODEL - Abdus Salam; Romi Faslah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the evaluation of the quality of Islamic Religious Education in Islamic educational institutions by applying the CIPP (Context, Input, Process, Product) model. The problem addressed in this paper concerns the variations in the quality of Islamic Religious Education practices, which are often influenced by institutional policies, teacher competence, curriculum implementation, and learning culture. The objective of this study is to describe how the CIPP model can serve as a systematic evaluation framework to ensure continuous quality improvement in Islamic Religious Education. This study employs a literature review approach by analyzing academic publications, books, and official policy documents relevant to quality assurance in Islamic educational institutions. The analysis shows that the CIPP model allows evaluators to comprehensively examine institutional readiness, available resources, the implementation of learning activities, and the outcomes achieved by learners. The conclusion indicates that the CIPP model provides a structured and measurable evaluation framework that aligns with the objectives of Islamic Religious Education, particularly in strengthening knowledge, faith, and ethical character. To be effective, the model requires institutional commitment, competent educators, and consistent follow-up evaluation.